On democratizing financial turmoil: a Minskian analysis of the subprime crisis - Luisa Fernandez; Fadhel Kaboub; Zdravka Todorova (Levy Economics Institute of Bard College, 2008)
The paper uses Minsky's financial instability hypothesis as an analytical framework for understanding the subprime mortgage crisis and for introducing adequate reforms to restore economic stability. We argue that the subprime crisis has structural origins that extend far beyond the housing and financial markets. We further argue that rising inequality since the 1980s formed the breeding ground for the current financial markets meltdown. What we observe today is only the manifestation of the ingenuity of the market in taking advantage of moneymaking opportunities, regardless of the consequences. The so-called democratization of homeownership rapidly turned into record-high delinquencies and foreclosures. The sudden turn in market expectations led investors and banks to reevaluate their portfolios, which brought about a credit crunch and widespread economic instability. The Federal Reserve Bank's intervention came too late and failed to usher in adequate regulation. Finally, the paper argues that a true democratization of homeownership is only possible through job creation and incomegeneration programs, rather than through exotic mortgage schemes.
Keywords: B52; B58; E12; E44; B52; G21; G24; 330; Minsky; financial instability; Wall Street; subprime mortgages; real estate; full employment; inequality